Rút gọn biểu thức sau: (4-3x)(2x-1)-2(3x-1)(1-2x)+(3x+1)(4-5x)

Question

Rút gọn biểu thức sau:
(4-3x)(2x-1)-2(3x-1)(1-2x)+(3x+1)(4-5x)

in progress 0
Anna 3 tháng 2021-09-10T03:45:28+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-09-10T03:46:39+00:00

    (4-3x)(2x-1)-2(3x-1)(1-2x)+(3x+1)(4-5x)

    = 8x-4-6x²+3x+10x-12x²-2-8x+4

    = -18x²+13x-2

    0
    2021-09-10T03:46:57+00:00

    $(-3x+4)(2x-1)+2(3x-1)(2x-1)+(3x+1)(-5x+4)$

    $= (2x-1)[-3x+4+2(3x-1)]+(3x+1)(-5x+4)$

    $= (2x-1)(3x+2)+(3x+1)(-5x+4)$

    $= 6x^2+x-2-15x^2+7x+4$

    $= -9x^2+8x+2$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )